The fiction of Margaret Atwood - Tolan, Fiona 1979- (Bloomsbury Academic, 2022)
"Margaret Atwood is one of the most significant writers working today. Her writing spans seven decades, is phenomenally diverse and ambitious, and has amassed an enormous body of literary criticism. In this invaluable guide, Fiona Tolan provides a clear and comprehensive overview of evolving critical approaches to Atwood’s work. Addressing all of the author’s key texts, the book deftly guides the reader through the most characteristic, influential, and insightful critical readings of the last fifty years. It highlights recurring themes in Atwood’s work, such as gender, feminism, power and violence, fairy tale and the gothic, environmental destruction, and dystopian futures. This is an indispensable companion for anyone interested in reading and writing about Margaret Atwood."
Keywords: Atwood, Margaret -- 1939-; Geschichte; Rezeption; Atwood, Margaret / 1939- / Criticism and interpretation; Canadian fiction / History and criticism; Atwood, Margaret / 1939-; Canadian fiction; Criticism, interpretation, etc; Literary criticism